If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P = a + -1(n + -1) * b Reorder the terms: P = a + -1(-1 + n) * b Reorder the terms for easier multiplication: P = a + -1b(-1 + n) P = a + (-1 * -1b + n * -1b) P = a + (1b + -1bn) Solving P = a + 1b + -1bn Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Simplifying P = a + 1b + -1bn
| 12x+4+2x=3 | | -1-(1+3n)=-(1-10n)-1 | | 3+6+4-2a= | | 651=-93x | | 9-4a=3a+9 | | 3x+-28+3x-30+x=33 | | 0.4=20 | | 6x+8=-82 | | 40+14x=2(-4j-13) | | -(-8x+8)+5x=-3x+24 | | -(x/7)=5 | | 72t^2-50=0 | | 0.24(6)+0.04x=0.12(12+x) | | 3x+1+(1/2)x+3=18 | | sin^2(3.14/4) | | 10a+3b+12=8a+8+b | | 7x+x-2=7x+4 | | (-3/2)(y-8)-1/6y | | 3/4(9)-8 | | 9x^2-65x-56=0 | | -46-10x=-136 | | 5a=3a-10 | | -6c+5=-13 | | 6x1/10 | | 85=-6x+4x | | 10m^5x^8-15m^3z^10=0 | | 3/5-(-10/11) | | 20x-5x+2=190 | | 3.9x=53 | | -4(x+9)-41=5-58 | | 3(3c-1)-6=4c+6 | | 9-3x-2x=6 |